Cytomegalovirus Management in Adult Hematopoietic Stem Cell Transplant Patients with Pre-Engraftment Viremia: A Single-Center, Retrospective, Descriptive Study. (4th October 2017) - Martin, Isabella; Avery, Robin; Gladstone, Douglas; Ambinder, Richard; Tucker, Noah; Valsamakis, Alexandra
Abstract: Background: Scant data exist regarding cytomegalovirus (CMV) viremia in hematopoietic stem cell transplant (HSCT) recipients during the pre-engraftment period. The goal of this study was to describe management of CMV in neutropenic adult HSCT patients at our institution, and to assess the possible impact of different quantitative CMV PCR tests (QPCRs). Methods: Post-HSCT monitoring at this center includes weekly CMV QPCR from plasma. Three different QPCR assays were used sequentially during the study period (1/2010–12/2015): two with lower limits of quantification (LLOQ) of 300 and 100 copies/mL through 4/2013, and after that the FDA-approved assay with LLOQ of 137 IU/mL. Medical records of first-time HSCT patients were reviewed. Pre-/peri-engraftment CMV was defined as detectable CMV DNA with [ANC] < 1000 cells/mm 3 . Information collected included demographics, donor/recipient CMV serostatus, conditioning regimen, CMV QPCR and ANC results, dates of CMV treatment, CMV disease within 100 days, and death within 6 months of HSCT. Data were analyzed with STATA v14. Results: Of 1151 total HSCT, 76 patients had a positive CMV QPCR when ANC < 1000 cells/mm 3 . CMV was first detected a median of 12 days (0–48) post-transplant, and was above LLOQ at a median of 28 days (0–49). 71/76 (93%) were treated at a median of 33 days post-transplant (range 4–105 days), most with valganciclovir (40) or ganciclovir (30); 1 received foscarnet initially. 5 patients with low-level viremia were monitored without treatment. At initiation of therapy, median CMV level was 1471 (range 159–22, 900) copies or IU/mL and ANC was 1202 (range 28–9680) cells/mm 3 . Median treatment duration was 34 days (range 9–392). Only 2 patients had possible tissue-invasive CMV disease. Conclusion: Ganciclovir and valganciclovir were used to treat most pre- and peri-engraftment CMV viremia, despite potential bone marrow toxicity. The LLOQ of different CMV QPCR tests did not affect the viral threshold for starting treatment. The time between first CMV DNA detection (median day +12) and initiation of treatment (median day +33) suggests clinicians waited for CMV DNA and/or ANC to rise before treating. With this deferred-treatment approach, the proportion of patients with tissue-invasive disease remained low. Disclosures: All authors: No reported disclosures.